Drivers of firm growth: Micro-evidence from Indian manufacturing - Nanditha Mathew (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2012)
The paper presents micro evidence on firm dynamics for enterprises in Indian Manufacturing sectors on the grounds of Prowess database provided by the Centre for Monitoring Indian Economy (CMIE) covering the period 1991-2010. The parameterization of the distributions of growth exhibit high level heterogeneity displayed among firms even within the same sector, which widens over time. The transition probabilities matrix reveals the coexistence of firms with very different characteristics and performance within sectors. Given the wide heterogeneities, the paper resorts to quantile regression to identify the differential effect of regressors at different deciles of the conditional distrubution.
Keywords: 330; Firm Dynamics; AEP Distribution; Heterogeneity; Quantile Regression